Criminal Law Enforcement in the Suppression of the Crime of Human Trafficking - Mar’ie Muhammad; Hambali Thalib; Salle Salle (Fakultas Hukum, Universitas Muslim Indonesia, 2026)
This study aims to analyze the regulation and enforcement of criminal law in combating the crime of human trafficking in Indonesia from a normative legal perspective. The research method employed is normative legal research using statutory and conceptual approaches through an examination of the 1945 Constitution of the Republic of Indonesia, Law Number 21 of 2007 on the Eradication of the Crime of Human Trafficking, the Criminal Code (KUHP), and the Criminal Procedure Code (KUHAP). The findings indicate that, normatively, Indonesia has established a relatively comprehensive legal framework through the Anti-Trafficking Law (UU PTPPO) as a lex specialis emphasizing both the punishment of perpetrators and the protection of victims. However, the effectiveness of law enforcement still faces various challenges, including the complexity of proving chain crimes, limited investigative capacity—particularly regarding digital evidence—disharmony in the application of legal provisions, weak inter-agency coordination, and suboptimal victim recovery mechanisms that risk causing revictimization. Effective criminal law enforcement requires the integration of repressive and restorative approaches through the implementation of a victim-centered approach, strengthening witness and victim protection mechanisms, enhancing technology-based evidentiary capacity, and promoting cross-sectoral as well as international coordination. Therefore, criminal law enforcement against human trafficking must be directed not only toward legal certainty but also toward substantive justice and the restoration of victims’ dignity within a human rights–oriented rule of law framework